Thomas Erastus oor die struktuur van die gemeenskap - Pont, A. D. (Hervormde teologiese studies, 1985)
Thomas Erastus on the church, the rulers and the community In this, largely descriptive paper, the views of Thomas Erastus (1520-1583) of Heidelberg, are discussed. Erastus' views on the church, the rulers and the community are put forward in his Treatise Explicatio gravissimae of 1568-69, published in 1589. It is clear that Erastus depends on the Zurich covenant-theology in his view that the community is essentially a Christian community ruled by the pius magistratus. In this community the church does not appear as a separate coetus or societas, but is ruled by the godly prince who rules according to God's law. Erastus' view gained popularity in the ecclesia AngUcam and was, to a certain extent, also a plea for the divine rights of kings.